Estudo de caso comparativo entre uma luminária LED e uma luminária convencional à vapor de sódio - Stocko, Joilson Luiz (2013)
In this work will be presented a case study comparing a luminaire LED and a sodium Vapor lamp. Three studies will be presented which are two comparisons and a history of illuminance. In comparison it has a comparative luminotécnico between a lamp and a luminaire LED imported sodium Vapor drawing on NBR 5101:2012. Another comparison is made for electrical criteria, but no measurements in sodium Vapor lamp, electrical measurements were taken from two LED lights, one domestic and one imported, based on the ANEEL Resolution 414 and IEC 61000-3-2. The record was held for national fixture, light engineering measures which were taken over two years with 6510 hours operating, check for depreciation and luminaire or evolution.